Food consumption habits of consumers in the Philippines: Changes amidst the pandemic - Jonathan Necor Tariga; Dyanika Paray Nolasco; Syrille Joyce Raspado Barayuga (International Journal of Public Health Science (IJPHS), 2021)
A quantitative descriptive strategy was applied to identify food patterns for Filipino consumers before, during and after the COVID-19 pandemic. Sampling was carried out using simple random sampling techniques. An electronic-questionnaire served as primary research instrument and was distributed through social media platforms to which 80 out of 250 responses were selected. Simple quantitative analysis such as mean value, frequency distribution and percentage were utilized. Results showed that the most of the respondent’s diet has wellness, social and psychological influence. Organic diet desires and self-cooking practices are continuing to grow. The study also showed that the essential aspects of food choice, health, quality and safety are increasingly being taken into account. The COVID-19 pandemic shifted the habits of food intake to healthier, influencing even the preference of consumed food. Thus, this study can be used as a theoretical guide especially for factors influencing the eating patterns during a pandemic. Ergo, food establishments can make use of the results to strategize to combat the COVID-19 pandemic by improving product quality on the basis of consumer needs and demands.